AI and digital out-of-home advertising in smart cities - Nikola VANGELOV (Smart Cities and Regional Development Journal)
The purpose of the text is to explore some of the possibilities that artificial intelligence (AI) offers to increase the effectiveness of digital out-of-home (DOOH) advertising campaigns. The object of analysis is the creation of advertising content, with special attention paid to personalized advertising formats. AI's ability to analyze information based on user behavior, as well as tools to optimize DOOH advertising campaigns, are also covered. Previous studies are also analyzed regarding outdoor advertising and smart cities. Through content analysis the main aspects of DOOH advertising and smart cities are analyzed, so that a proposition could be made regarding their integration aiming at razing ads visibility and thus their effectiveness. The examples studied may lead to a better understanding of this relatively new and constantly evolving technology in the field of advertising. This is useful both for consumers who want relevant and interactive advertising content, and for organizations aiming to optimize advertising efforts and campaign effectiveness. The paper could be of interest to practitioners, academicians and students in the field of marketing, advertising, sales promotion and brand communication.